Exposure of orthodontically Maxillary impacted canine by diode laser (810_980)Nm(comparative study between palatal and buccal position) - Alaa faiz Abdullah1,; Soudad Salman Ahmed,; Balsam Saadi Abdul Hameed, (Iraqi Journal of Laser, 2024)
Background: Diode lasers(810+980) provide deep soft tissue penetration and have minimal interaction with tooth-hard tissues and excellent coagulation/haemostasis.Objective: The aim of the current research was the exposure of maxillary buccally impacted canines by diode laser(810+980)nm in comparing palatally impacted canines depending on these parameters (pain, oedema, healing time).Materials and methods: All patients with an impaction of the maxillary canines, such as buccal or palatal impaction, were required to be exposed. They were separated into two groups: one with seven patients in the buccal position and another with seven patients in the palatal position. Systemically healthy patients in two groups had treatment with diode lasers (980+810)mn. This study did not allow the inclusion of patients who were pregnant or in any other medically compromised patients. Pain, edema, and healing were recorded using follow-up scores on the first, second, and fifth days as well as the first and second week following surgery and statistically examined.Results: The age mean in this study five male and nine female was 26.2. P ≤ 0.05 was designated as the significant level..patients with buccally impacted canines exposure experience less pain, less swelling, and healing more quickly than patients with palatally impacted canines.Conclusion: Patients with buccally impacted canines had less pain and swelling and faster wound healing than patients with palatally impacted canines when exposed.